Corticotomy With a Palatal Bone-Borne Retractor for Correcting Severe Bimaxillary Protrusion. Issue 1 (January 2018) - Noh, Min-Ki; Kim, Young-Jun; Chung, Kyu-Rhim; Kim, Seong-Hun; Nelson, Gerald
Abstract : Background: This article presents an alternate surgical treatment method to correct a severe anterior protrusion in the adult patient with an extremely thin alveolus. Methods: In the maxilla, a wide linear corticotomy was performed under local anesthesia. Cortical alveolar bone of the upper first bicuspids area was widely removed. Orthopedic force for bony block movement was applied by a palatal bone-borne type retractor supported by skeletal anchorage. Residual extraction space closure was performed by biocreative orthodontics strategy (BOS). In the mandible, an anterior segmental osteotomy (ASO) and extraction of 1st premolars were performed under local anesthesia. Results: In the maxilla, bony block movement followed by the wide linear corticotomy with a palatal bone-borne type retractor was implemented without complications. Remaining extraction space after the bony block movement was closed effectively by BOS. In the mandible, anterior segmental retraction was achieved effectively by ASO. Conclusions: Wide linear corticotomy with a palatal bone-borne type retractor and ASO under local anesthesia can be an effective alternative to orthognathic surgery in adults with protrusion and an extremely thin alveolus. The biocreative strategy also provides a simple and effective method to retract the 6 anterior teeth.